2020
DOI: 10.1111/jth.14720
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of confirmed antiphospholipid syndrome in 18‐50 years unselected patients with first unprovoked venous thromboembolism

Abstract: Background Antiphospholipid syndrome (APS) is an acquired thrombophilia disorder with prevalence not completely known in patients with first unprovoked venous thromboembolic events (VTE). Recent data suggest that the management of some APS patients should be different from that of patients with other thrombophilia. Our aim was to estimate the prevalence of APS in a community‐based cohort of patients with a first unprovoked VTE. Methods We conducted a cross‐sectional study analyzing data from our computer assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 26 publications
4
24
0
2
Order By: Relevance
“…The thrombophilia prevalence rates in our study concurred with these pre‐established prevalence rates for high‐risk heritable thrombophilias, with protein C and S deficiency reported to be present in up to 7% and 4.8%, respectively, of patients with VT at unusual site 29 . Of the 39 patients, three had persistent aPL, which have been estimated to be present in approximately 10% of patients with VTE 30,31 . These women, however, were offered but did not receive treatment with LMWH.…”
Section: Discussionsupporting
confidence: 88%
“…The thrombophilia prevalence rates in our study concurred with these pre‐established prevalence rates for high‐risk heritable thrombophilias, with protein C and S deficiency reported to be present in up to 7% and 4.8%, respectively, of patients with VT at unusual site 29 . Of the 39 patients, three had persistent aPL, which have been estimated to be present in approximately 10% of patients with VTE 30,31 . These women, however, were offered but did not receive treatment with LMWH.…”
Section: Discussionsupporting
confidence: 88%
“…31 A cross-sectional study of 491 patients with a first unprovoked VTE also found that 9% (44/491) of patients met criteria for APS, with 1.4% (7/491) being persistently triple aPL-positive. 32 These observations raise the issue of the optimal timing for aPL testing after a first VTE.…”
Section: Direct Oral Anticoagulants (Doacs)mentioning
confidence: 99%
“…In contrast, triple aPL-positivity persists in the majority of patients, 36,37 although it occurs in only a minority of patients with a first VTE. 31,32 Guidance regarding the timing of thrombophilia testing including testing for APS exists. 38 It may be preferable to defer screening for aPL for most patients with a new VTE in the acute setting.…”
Section: Direct Oral Anticoagulants (Doacs)mentioning
confidence: 99%
“…Some reports describe an incidence of 5 cases per 100,000 population per year and a prevalence of 40–50 per 100,000 population (1,3–6). In several recent studies, investigators attempted to estimate the prevalence of aPLs in different cohorts, such as in young patients with stroke (7), patients with pregnancy morbidity, stroke, myocardial infarction, and deep vein thrombosis (4), and patients with a first unprovoked thrombosis (8). To date, APS meets the definition of a rare disease as described by Holué (prevalence ≤5 per 10,000 population) (9).…”
Section: Figurementioning
confidence: 99%